Glucose transport in vesicles reconstituted from Saccharomyces cerevisiae membranes and liposomes. - Ongjoco, R (1987)
Glucose transport activity was reconstituted into liposomes by the freeze-thaw-sonication procedure from unextracted Saccharomyces cerevisiae membranes and preformed phospholipid liposomes. Fluorescence-dequenching measurements with octadecylrhodamine B chloride (R18)-labeled membranes showed that the yeast membrane lipids are diluted by the liposome lipids after the freeze-thaw-sonication procedure. At lipid-to-protein ratios greater than 75:1, vesicles with single transporters were formed. Reconstituted specific activity was increased at least twofold if the liposomes contained 50 mol% cholesterol. A further increase in specific activity, from 3- to 10-fold, was achieved by fractionation of the membranes on a Renografin gradient before reconstitution. Examination of the fractions from the Renografin gradient by sodium dodecyl sulfate-gel electrophoresis showed a parallel enrichment of glucose transport activity and a number of proteins including one with an apparent Mr of ca. 60,000, which might be the glucose transporter. Finally, preliminary kinetic analysis of glucose transport activity in vesicles reconstituted at a high lipid-to-protein ratio gave a Vmax of ca. 2.8 mumol/mg of protein per min at 23 degrees C and a Km of ca. 8 mM. The latter value corresponds to the kinase-independent, low-affinity component of glucose transport observed in wild-type cells.